ON THE PROBLEM OF SYSTEMIC NATIONAL TERMINOLOGY - Kasymova Айсұлу Молдағұлқызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
Problem questions arising up during translation of normatively-legal acts are examined in the article.